The individual differentiation and Implications In Islamic Education Models - Amilia Afnani; Achmad Baihaqi (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Background: The concept of individual-based learning offered by the west, has not been able to be applied maximally by majority of Islamic Religious Education teachers. The concept of Islamic education based on individuals is expected to be obtained by further studying the guidelines of Islamic teaching (Al Qur'an and Hadith). This study aims at examiney the literature, articles, and documents of research results on Islamic perspectives on individual differences and their implications in education. The method used was a literature review, articles were collected using various search engines. From a variety of literature, it showsed that various models of Islamic education that distinguish individuals have not fully influenced, why in its application still seems passive. Conclusion: The Islamic Education Model that needs to be differentiated by individuals must be realized and evaluated and continuously developed.